TREATMEN DAN KONDISI PSIKOLOGIS MUALLAF - Hafidz Muhdhori (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
Religious conversion is the act of conversion will be undertaken someone as a real form on the turmoil of one’s soul on a belief and trust in the new religion. When someone does a religious conversion means he has left the old religion and the move to the new religion, someone who has embraced the religion of Islam is usually often experience psychological dilemmas that require an understanding of the community. Things like this very important as a concern in the community, for a muallaf tranquility and comfort in the midst of life in society is very important, with tranquility and comfort and guidance even good reception from the public that will be it as a reinforcement of the psychological condition of a muallaf, thereby strengthening the grip and confidence in their beliefs. This article aims to find a convert and a form of psychological treatments given to the muallaf as a form of strengthening the psychological condition muallaf. The method used in this research is qualitative descriptive, with the techniques of data collection using interviews, observation, and documentation. by taking four samples of two people from Christianity Catholic and two Protestant Christians. With the result object embraced Islam willingly and there is no pressure at all from outside himself. at the beginning of their conversion find their pressure coming from family, relatives, close friends, and the community, from the start in angry, insulted, reviled, and up to physical violence. So that it resulted in the disrupt tion of psychological conditions muallaf.